2018
DOI: 10.1080/21501203.2017.1421592
|View full text |Cite
|
Sign up to set email alerts
|

Fungicidal versus fungistatic therapy of invasive Candida infection in non-neutropenic adults: a meta-analysis

Abstract: The purpose of this study was to determine whether fungicidal versus fungistatic pharmacotherapy of invasive candidiasis/candidemia yields superior outcomes.Data sources included MEDLINE (1966–June 2017), EMBASE (1980–June 2017), PubMed (1966–June 2017), Global Health-Ovid (inception to June 2017), LILACS Virtual Health Library (inception to June 2017) and the Cochrane Central Register of Controlled Trials (to 2nd quarter 2017). The ClinicalTrial.gov database, the SCOPUS database, SIGLE (System for Information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…The residual growth of the WT strain was present but limited at concentrations from 1 µg/mL fluconazole and 0.05 µg/mL ketoconazole upwards (MIC 50 = 1 and 0.015 µg/mL for fluconazole and ketoconazole, respectively). According to literature, this can be attributed to the fungistatic properties of azoles [23]. The growth of the WT strain treated with azoles (≥1 µg/mL fluconazole and ≥0.05 µg/mL ketoconazole, Figure 1B and data not shown) was slower than that of KS028.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The residual growth of the WT strain was present but limited at concentrations from 1 µg/mL fluconazole and 0.05 µg/mL ketoconazole upwards (MIC 50 = 1 and 0.015 µg/mL for fluconazole and ketoconazole, respectively). According to literature, this can be attributed to the fungistatic properties of azoles [23]. The growth of the WT strain treated with azoles (≥1 µg/mL fluconazole and ≥0.05 µg/mL ketoconazole, Figure 1B and data not shown) was slower than that of KS028.…”
Section: Resultsmentioning
confidence: 63%
“…The ERG11 gene is considered essential to C. albicans viability [35], despite Erg11p blockage by azoles having a fungistatic rather than fungicidal effect [23]. Sanglard et al [36] showed that C. albicans erg11Δ/Δ mutants could be produced from either an erg3Δ/Δ background or as a result of mitotic recombination after culturing ERG11/erg11Δ heterozygotes in the presence of amphotericin B.…”
Section: Discussionmentioning
confidence: 99%
“…Initial analysis revealed that the chelates have a fungicidal activity at higher concentrations and fungistatic activity in lower doses, a profile previously described for antibiotic drugs such as fluconazole, voriconazol and caspofungin (Meletiadis et al, 2007;Venisse et al, 2008;Domán et al, 2015;Lee and Lee, 2018). A recent meta-analysis suggests that fungicidal drugs might have an advantage regarding early therapeutic success (Kumar et al, 2018), making the fungicidal properties of the chelates a possible advantageous property. The current virulence studies using G. mellonella revealed that fungal inoculum size was directly associated with the infection outcome and that C. haemulonii was less virulent than C. albicans, with 10-times more C. haemulonii cells required to obtain similar mortality rates.…”
Section: Discussionmentioning
confidence: 88%
“…The risk of resistance development in fungal pathogens is greatly reduced with fungicidal agents [32]. Notably, PAF and PAFB show fungicidal potential on the wide-spread opportunistic human pathogen C. albicans killing planktonic cells and inhibiting biofilms ( Figure 3) [11,14].…”
Section: Antimicrobial and Antiviral Activitymentioning
confidence: 99%